A Material Showing Colossal Positive and Negative Volumetric Thermal Expansion with Hysteretic Magnetic Transition. Issue 42 (13th September 2017) - Hu, Ji‐Xiang; Xu, Yang; Meng, Yin‐Shan; Zhao, Liang; Hayami, Shinya; Sato, Osamu; Liu, Tao
Abstract: It is an ongoing challenge to design and synthesize magnetic materials that undergo colossal thermal expansion and that possess potential applications as microscale or nanoscale actuators with magnetic functionality. A paramagnetic metallocyanate building block was used to construct a cyanide‐bridged Fe‐Co complex featuring both positive and negative colossal volumetric thermal‐expansion behavior. A detailed study revealed that metal‐to‐metal charge transfer between 180 and 240 K induced a volumetric thermal expansion coefficient of 1498 MK −1 accompanied with hysteretic spin transition. Rotation of the magnetic building blocks induced change of π⋅⋅⋅π interactions, resulting in a negative volume expansion coefficient of −489 MK −1, and another hysteretic magnetic transition between 300 and 350 K. This work presents a strategy for incorporating both colossal positive and negative volumetric thermal expansion with shape and magnetic memory effects in a material. Abstract : We got both kinds of expansion : A Fe−Co layered network was synthesized. This material exhibits colossal positive and negative thermal expansion (PTE and NTE) at different temperature regions accompanying hysteretic magnetic transitions.